Romanian Adaptation and Validation of the Multidimensional Psychological Flexibility Inventory - Marian Stefan, Crisan Iulia, Varga Stefan Sergiu, Isbasoiu Andreea Bogdana (Evaluation & the Health Professions, 2026)
The Multidimensional Psychological Flexibility Inventory (MPFI) is a complex self-report measurement tool designed to assess Acceptance and Commitment Therapy’s (ACT) Hexaflex model components of psychological flexibility and inflexibility. There is a lack of literature on the invariance of the MPFI and its discriminant validity in relationship to second-wave therapy concepts such negative automatic thoughts. In this study, we present a Romanian adaptation and validation of the MPFI performed on a sample of 1109 participants from the general population. The results indicated an adequate fit to the data of the original MPFI factor model, high internal consistency levels, the ability to be invariant across levels of gender and age, and supported the MPFI’s convergent, and discriminant. Some theory incongruent correlations emerged between MPFI dimensions and acceptance and experiential avoidance that suggest the need for further refinement of the MPFI. We discuss this unexpected correlation in relationship to explanatory factors such as the COVID lockdown context, personality, and age. Altogether, our results indicate that the Romanian version of the MPFI is a psychometrically sound instrument that can be used to study the Hexaflex ACT model and to evaluate psychological flexibility and inflexibility and their sub-processes in practice.
Paid by Anelis Plus